Nilai Simbolik Tata Rias Busana dalam Ranah Seni Pertunjukan - Kompiang Gede Widnyana (Journal on Education, 2023)
Clothing is a very important factor in Balinese Dance. Seeing this development, of course, requires quality improvement and adequate facilities, for example: stage venues, quality production, music arrangements and what is no less important is the design of clothing to support the character of each role. To appear on stage or stage shows, the role of clothing determines the success of a show, therefore this part is growing rapidly in line with the development of the show. This study uses a qualitative method. Based on this research, a conclusion can be drawn that; The symbolic value of Balinese dance clothing in performing arts can essentially provide identity and strengthen the character of a role. Clothing as something that is important in a performance is closely related to the use of other elements such as the dance movements used.